Design and Evaluation of Drug Release Kinetics of Theophylline from Co-processed Colocasia esculenta Gum. - Nnamani, Nnabuike D.; Kashimawo, Adesegun J. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Adjuvants are co-formulated in dosage forms to modify, improve or control the release rate of active pharmaceutical ingredients to achieve optimal drug concentration in the plasma or the site of action, modify onset of action and or duration of action. One such adjuvant is the gummy polysaccharide obtained from Colocosia esculenta. The aim of this study is to investigate the release kinetics of Theophylline from the dispersion made from Colocosia esculenta co-processed polymer matrix. The polysaccharide gum from Colocosia esculenta was extracted with water and precipitated with acetone. The purified polymer isolated was investigated for its drug release properties using Theophylline in form of Theophylline – Colocosia esculenta polysaccharide gum matrix. Theophylline interaction with the gum was investigated using Fourier Transform Infra Red (FT-IR) studies. Various concentrations of dispersion of Theophylline was prepared ( 1.0, 2.5, 5.0 and 7.5, labelled A,B,C and D respectively) in the polymer matrix and were evaluated for drug release using dissolution studies. The FT-IR results indicate no strong chemical interaction between theophylline and Colocasia esculenta gum. The dissolution rate of Theophylline in A, B and C follow the first order release model with coefficient of correlation (r2) of 0.9153, 0.91 and 0.9679 respectively while release kinetics of theophylline from batch D best fits Higuchi model with r2 of 0.9849 and Hixson Corwel model,with r2 of 0.9785. The drug release mechanism of batches A, B, and C,are directly proportional to the concentration theophylline in the matrix. The theophylline release from batch D is indicative of control-release matrix that releases drug mainly by diffusion from matrix, and is dependent on the volume of exposed dosage surface. Thus, higher concentration of Colocasia esculenta gum in theophylline-gum matrix led to controlled or modified release of Theophylline.